The Who, Where, What, How and When of Market Entry. (22nd May 2019) - Markman, Gideon D.; Gianiodis, Peter; Tyge Payne, G.; Tucci, Christopher; Filatotchev, Igor; Kotha, Reddi; Gedajlovic, Eric
Abstract: This introductory, along with the eight articles contained within this Special Issue, highlights and brings greater clarity to entrant‐incumbent interactions and to firm movement – when entrants traverse market territories for the creation and/or delivery of offerings, where 'markets' include service or product categories, technology or resource spaces, industries, sectors and/or geographies. Collectively, this Special Issues explains that firm movement across market boundaries is highly consequential, influencing resource‐capability mixes inside firms, interfirm relations, market logic and industry value chains, and of course, people, communities and even nations. Specifically, we develop a field‐wide perspective of market entry by expanding on the framework of market entry that Zachary and his colleagues developed (Zachary et al., 2015) – i.e., the who (players such as incumbents, entrants, suppliers, etc.), when (the timing and sequence of entry), how (the strategy, resources, capabilities, etc.), where (the space of entry) and what (product, service, business model, etc.) – to include two additional categories: complements (networks, platforms, ecosystems) and non‐market elements (government, political, social and cultural arrangements). We also summarize the eight highly diverse and insightful articles that make this Special Issue, and conclude with a discussion to highlight foundational questions that point to new directions in future research in this field. In sum, we hope to inspire scholars to go beyond counting outcomes (e.g., entry/exit rates, or profiling successful versus unsuccessful entrants), to consider contexts, processes and contingencies (e.g., cost, time, collaboration, competition, interfirm relations, etc.) and to discover boundary conditions that inform a theory of market entry.